2017
DOI: 10.1007/s00223-017-0303-2
|View full text |Cite
|
Sign up to set email alerts
|

Obese Versus Normal-Weight Late-Adolescent Females have Inferior Trabecular Bone Microarchitecture: A Pilot Case-Control Study

Abstract: Though still a topic of debate, the position that skeletal health is compromised with obesity has received support in the pediatric and adult literature. The limited data relating specifically to trabecular bone microarchitecture, however, have been relatively inconsistent. The aim of this pilot cross-sectional case-control study was to compare trabecular bone microarchitecture between obese (OB) and normal-weight (NW) late-adolescent females. A secondary aim was to compare diaphyseal cortical bone outcomes be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Liu et al also reported 3T MR images (pixel size 0.180 mm × 0.180 mm, acq. time 9:18 min) of 92 distal femurs divided in three groups (without osteoarthritis, mild osteoarthritis, and severe osteoarthritis) reporting progressively lower BVF and higher erosion index from healthy patients to those affected by severe osteoarthritis [ 108 ], extending previous results [ 109 , 110 , 111 ].…”
Section: Mri Based Approachsupporting
confidence: 70%
See 1 more Smart Citation
“…Liu et al also reported 3T MR images (pixel size 0.180 mm × 0.180 mm, acq. time 9:18 min) of 92 distal femurs divided in three groups (without osteoarthritis, mild osteoarthritis, and severe osteoarthritis) reporting progressively lower BVF and higher erosion index from healthy patients to those affected by severe osteoarthritis [ 108 ], extending previous results [ 109 , 110 , 111 ].…”
Section: Mri Based Approachsupporting
confidence: 70%
“…The MRI potential for the bone microstructure has also been assessed in vivo in anatomical regions more affected by osteoporosis, i.e., tibiae and radii, vertebrae [ 65 , 117 , 118 ], distal [ 18 , 108 , 109 , 111 , 119 ], and proximal femurs [ 60 , 71 , 72 ]. Microarchitectural parameters extrapolated from 3T MRI (0.156 mm × 0.156 mm × 0.5 mm) and compared to HR-pQCT of tibiae and radii of 11 healthy volunteers showed good correlation for BVF (r = 0.83) and Tb.Sp (r = 0.7) in tibiae and good correlation for all the microarchitecture parameters investigated in radii (r = 0.65, 0.95, 0.83, and 0.63 for BVF, Tb.N, Tb.Sp, and Tb.Th respectively) [ 77 ].…”
Section: Mri Based Approachmentioning
confidence: 99%
“…In a cross-sectional analysis of nondiabetic postmenopausal women, higher levels of insulin resistance were associated with lower cortical bone volume, independent of age and weight[172]. Consistently, female obese late-adolescents had worse trabecular bone microarchitecture at the radius and tibia as compared with non-obese controls, as well as lower bone volume and estimated bone strength[173]. T2D diabetes and insulin resistance are almost invariably associated with obesity and increased central adiposity, which reflects increased VAT.…”
Section: Advanced Glycation End Products-bone Matrix In Diabetesmentioning
confidence: 99%
“…A complex relationship has been described between adiposity and bone development. Numerous studies have proposed that fat mass has a substantial effect on bone, not only due to increased mechanical loading [ 10 ] but also due to the metabolic action of bone–related hormones that are secreted or regulated by adipocytes [ 11 ]. However, excessive fat mass may negatively influence bone remodeling through the action of inflammatory cytokines that are released from visceral adipocytes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive fat mass may negatively influence bone remodeling through the action of inflammatory cytokines that are released from visceral adipocytes [ 12 ]. In this sense, after accounting for lean mass, adiposity seems to be a negative predictor of bone mass in youth [ 10 , 13 ]. Moreover, from a nutritional point of view, dietary intake is an important modifiable factor for both fat mass and bone health, accordingly normal bone metabolism requires a sufficient amount of nutrients, such as magnesium, calcium, phosphorus, vitamin D, potassium and proteins [ 14 ] also, nutrients such as calcium may play a significant role in decreasing fat mass [ 15 ].…”
Section: Introductionmentioning
confidence: 99%